EXPLORING THE COMPLEXITIES OF BILINGUAL APHASIA: IMPLICATIONS IN THE CONTEXT OF NEUROLINGUISTICS - Nasrullah, Riki; Mintowati, Mintowati; Yohanes, Budinuryanta; Suganda, Dadang (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2025)
Aphasia, a complex communication disorder resulting from brain damage, causes difficulties in understanding and using language. The phenomenon of bilingual aphasia is challenging due to its complexity in understanding and rehabilitating language disorders. In the globalization era, the dual-speaking population's growth is increasing. However, our understanding of bilingual aphasia is still limited. Therefore, in-depth and systematic research is needed to guide bilingual aphasia's diagnosis, treatment, and rehabilitation. This study used a rigorous literature review method, with a thematic search and analysis of relevant studies on bilingual aphasia. Symptom profiles, risk factors, pathophysiology, and rehabilitation strategies were comprehensively reviewed. The thematic analysis of the literature revealed diverse symptom profiles in individuals with bilingual aphasia and associated risk factors and pathophysiological mechanisms. In addition, this study examined effective rehabilitation strategies appropriate to the characteristics of bilingual aphasia. This research has important implications in neurolinguistics and aphasiology, improving the accuracy of diagnosis, development of appropriate interventions, and effective rehabilitation planning. The results make valuable contributions to clinical practitioners, researchers, and educators in providing better care and support for individuals with bilingual aphasia. In addition, this study also enriches our understanding of the complexity of language and the brain-language connection at large.